Peranan Humas Pemerintah Provinsi Sumatera Selatan Dalam Meningkatkan Hubungan Baik Dengan Media Massa - Satria, Ega Puza; Saswita, Saswita; Febrianza, Muhammad (@-Publik: Jurnal Administrasi Publik, 2023)
Public Relations (PR) is all efforts and endeavors carried out with the aim of shaping the perception and judgmental responses of others. Issues within PR include instances where reports on development programs by some media are turned into advertorials (ads) without prior confirmation from PR, PR's limited ability to prevent unbalanced and inaccurate information in the news, a lack of scheduled press meetings with mass media, and suboptimal provision of press releases to journalists. The objective of this research is to analyze the role of the Public Relations of the South Sumatra Provincial Government in improving relations with the mass media. Based on the research results, the Public Relations and Protocol Division of the South Sumatra Provincial Government plays its role effectively in enhancing relations with the mass media, which includes understanding and serving the media collaboratively and efficiently. Regarding building the organization's trustworthy reputation in the media, PR achieves this by providing materials and engaging in overall two-way communication effectively. Ensuring the provision of adequate and accurate information, PR and Protocol are required to excel in writing press releases, which has been carried out effectively. In terms of cooperating in the provision of materials and information through press conferences, PR has also been doing well. Additionally, providing verification facilities with dedicated media rooms has been effective. Building strong personal relationships with the media, as seen through the available human resources and advertorial placements in media collaborations, has been satisfactory as well.